Community Perceptions of Police Body-Worn Cameras: The Impact of Views on Fairness, Fear, Performance, and Privacy - Crow, Matthew S. (Criminal justice and behavior, 2017)
Despite relatively little extant research, efforts to expand the use of body-worn cameras (BWCs) in policing are increasing. Although recent research suggests positive impacts of BWCs on reducing police use-of-force and citizen complaints, little is known about community members’ perceptions of BWCs. The current study examined perceptions of residents of two Florida counties and found a large majority of respondents supported the use of BWCs. Structural equation modeling was utilized to examine factors that influence views of BWCs. Findings indicate that positive perceptions of police performance and more police interaction were associated with greater perceived benefits of BWCs, whereas concerns about the privacy reduced perceived BWC benefits. Respondents’ views of procedural fairness and crime concern were indirectly related to perceptions BWC benefits. Non-White and younger respondents were indirectly less likely to perceive benefits. Implications of these findings and future directions for research are discussed.